The Influence of Strategic Environment, Public Trust, and Entrepreneurial Orientation on Competitive Advantage and Company Performance (Studies on Batik Companies in Tuban) - Yudi Supiyanto; Henny Sri Astuty; M. Yusuf (Procedia of Social Sciences and Humanities, 2021)
This study has the following objectives: Specifically, this researcher aims to prove and analyze whether:Strategic Environment, Public Trust, and Entrepreneurial Orientation influenced on Competitive Advantage and Company Performance. The population is batik SMEs belonging to the Tuban batik center totaling 84 SMEs batik and samples using the snowball sampling method and the number of samples are 84. To retrieve data using the questionnaire method and data analysis using path analysis. The results showed the following findings: 1. The strategic environment has a significant effect on competitive advantage 2. Public trust has a significant effect on the competitive 3. Entrepreneurial orientation has a significant effect on the competitive advantage 4. Strategic environment, public trust, and entrepreneurial orientation simultaneously have a significant positive effect on competitive advantage, 5. The strategic environment has a significant effect on the performance of batik companies, 6. Public trust has a significant effect on the performance of batik companies,7. Entrepreneurial orientation has a significant effect on the performance of batik companies, 8. Competitive advantage has no significant effect on the performance of batik companies, 9. The strategic environment, public trust, and entrepreneurial orientation and excellence simultaneously have a significant effect on the performance.